2014
DOI: 10.1007/s00330-014-3267-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI patterns of Nissen fundoplication: normal appearance and mechanisms of failure

Abstract: MRI offers simultaneous morphological and functional imaging in one diagnostic method. MR fluoroscopy offers the possibility to identify the wrap position. MRI enables a non-invasive diagnosis, providing detailed information for the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Therefore, it is not surprising that MRI achieves better results than endoscopy in diagnosing the location of the wrap or even its disruption [20]. Magnetic resonance imaging was able to confirm the correct position in 93% of patients and wrap disruption in all patients, when compared with the intraoperative results of the revision surgery [20]. In another study where endoscopy was used as a reference test, real-time MRI yielded an excellent sensitivity of 92%, with a specificity of only 17% [22].…”
Section: Impact Of Swallowing Mri In Failed Larsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is not surprising that MRI achieves better results than endoscopy in diagnosing the location of the wrap or even its disruption [20]. Magnetic resonance imaging was able to confirm the correct position in 93% of patients and wrap disruption in all patients, when compared with the intraoperative results of the revision surgery [20]. In another study where endoscopy was used as a reference test, real-time MRI yielded an excellent sensitivity of 92%, with a specificity of only 17% [22].…”
Section: Impact Of Swallowing Mri In Failed Larsmentioning
confidence: 99%
“…However, a "Toupet" fundoplication (270°circumference) can mimic a partial disruption of a Nissen fundoplication (360°complete circumference). Swallowing MRI has the major advantage of combining anatomical with functional information, enabling the assessment of esophageal dysmotility after fundoplication [20,22]. A reduction of propulsive contractions and a bolus transit time more than 20 s are a strong indicator of esophageal dysmotility [20].…”
Section: Wrap Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of MRI in studying oesophageal motility has been looked at and compared with high-resolution manometry to diagnose achalasia 36 and observe functional and anatomical information in Nissen fundoplication. 37 Both studies had subjects swallowing liquids whilst undergoing MRI, acquiring images using fast spinecho and cine bSSFP sequences. Studying 11 suspected achalasia patients and 3 control subjects, the authors concluded that MRI was safe and feasible for the diagnosis of achalasia.…”
Section: Evaluation Of Gi Motility and Movement Of Chyme By Mrimentioning
confidence: 99%
“…Partial or complete disruptions of the fundoplication sutures are demonstrated by a partial or missing wrap, combined with slipping of the gastric fundus or a paraesophageal hernia . A new imaging method, MR fluoroscopy, has shown promising results for the exact localization of dislocated fundoplication wraps …”
Section: Postoperative Esophagusmentioning
confidence: 99%